Policy-practice disconnect in climate disaster response: The case of the Zimbabwe Republic police during cyclone idai - Fungai Hwacha; Mahawan Karuniasa; Wezia Berkademi (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: Climate-induced disasters are testing the institutional limits of law enforcement agencies in sub-Saharan Africa, yet police forces remain peripheral to formal disaster risk governance. Cyclone Idai (March 2019) devastated the Chimanimani District of Zimbabwe, exposing critical gaps in the translation of national climate and disaster policies into ground-level action. This study examines the operational experience of the Zimbabwe Republic Police (ZRP) during the cyclone response, probing the disconnect between formal policy mandates and actual field performance. Methods: A qualitative case study design was used, grounded in semi-structured open-ended questionnaires administered to 15 purposively selected informants, including ZRP officers, government stakeholders, community leaders, and non-governmental organizations. Thematic analysis following Braun and Clarke’s six-stage framework was applied, with triangulation against key national policy documents, including Zimbabwe’s National Climate Change Response Strategy (2017), the National Disaster Risk Management Policy (2013), and the Civil Protection Act [Chapter 10:06]. Findings: All 15 participants (100%) reported that infrastructure collapse, destroyed roads, and bridges were an overriding constraint on police mobility, while 73% cited a total communication network failure. ZRP officers performed broad humanitarian roles, including search and rescue (86.6%), retrieval of the deceased (46.6%), and security of relief supplies (53.3%), operated with severe resource deficits and without climate-specific training. Communities praised the personal dedication of officers while directing frustration squarely at institutional and governance failures. Policy frameworks existed in name but had not been operationalized into routine training, equipment procurement, or coordinated pre-disaster planning. Conclusion: A deep policy-practice disconnect defines Zimbabwe’s disaster response architecture. Effective climate resilience requires the ZRP to be repositioned from reactive responders to proactive participants in national disaster governance, supported by decentralized authority, dedicated funding, and mandatory disaster training. The study proposes a Disaster Adaptive Response (DAR) model to guide this transition. Novelty/Originality of this article: This is the first empirical study to center police institutional capacity within Zimbabwe’s climate disaster governance, advancing the DAR model as an anticipatory framework for law enforcement-led disaster response in low-resource contexts.